Seed dormancy and germination responses of cannabis landraces to various pre-treatments - Langa, Sabeliwe; Magwaza, Lembe Samukelo; Mditshwa, Asanda; Tesfay, Samson Zeray (Elsevier, 2024)
The current study evaluated the effectiveness of different pre-treatments for dormancy breaking and seed germination of five cannabis landraces. These landraces were collected from local growers in three regions of KwaZulu-Natal Province in South Africa, namely, Bergville (B), Hammersdale (H), and Ladysmith (L). Each genotype was assigned an alphabet and number based on where the seed material was collected. The five landraces were as follows, ‘B1’, ‘K1’, ‘H1’, ‘L1’, and ‘L2’. The study was conducted using various pre-treatments, including potassium nitrate (KNO3), hydrochloric acid (HCL), hot water (HW) at 70 °C, nitric acid (HNO3), dry prechilling at 10 °C, gibberellic acid (GA3), sulfuric acid (H2SO4), and water, which served as the control. Before the germination test, the seed viability of cannabis landraces was assessed using the tetrazolium chloride (TCC) test. Afterward, the seeds were germinated in Petri dishes with cotton pads moistened with distilled water for five (5) days. The study was later validated under tunnel conditions. The parameters such as germination percentage, germination rate, seedling length, and seed vigour index of the germinated seeds were then measured. The landraces, dormancy breaking treatments, and their interactions showed significant differences (p < 0.001) in germination percentage, germination rate index, seedling length, and seed vigour index under both laboratory and tunnel conditions. In summary, GA3, KNO3 and prechilling were the most effective pre-treatments to improve the germination and seedling growth of cannabis genotypes and breaking seed dormancy. Therefore, it was concluded that cannabis genotypes had physiological dormancy.
Keywords: Cannabis; Dormancy breaking; Germination enhancement; Landrace